(untitled) (Estudos em Design, 2015)
The present study attempts an analysis of work situations Room Collection Donors and its relation to the health of workers in the approach of Ergonomics and Ergology. The method used was based on Ergonomic Work Analysis (EWA) and the techniques of participant observation, field diary and questionnaire (INSATS-Br.). Complaints of workers pains are related to blood collection, the organization of work and the amount of treated donors. We developed a prototype of blood collection table for transforming activity.